Tinjauan Pelaksanaan Review Berkas Rekam Medis Sesuai Standar Manajemen Informasi Dan Rekam Medik (MIRM 13.4) Di Rumah Sakit Imelda Pekerja Indonesia Tahun 2020 - Esraida Simanjuntak; Mustamil Alwi Dasopang (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
One of the parameters for determining the quality of health services in the hospital is data or information from good and complete medical records. Medical records are an important part of helping the implementation of service delivery to patients at the hospital. Standards relating to medical records in SNARS Edition 1 are in the group of hospital management standards, namely Medical Record Information Management (MIRM) regarding medical record document processing including provision, filling of medical records and reviewing medical records. This research method is descriptive with the method of observation. When this research was conducted in July 2020 at the Imelda Hospital Worker Indonesia Medan. The population taken was 705 medical record documents while the sample in this study was 87 medical record documents. Based on the results of the study, in the review the accuracy of returning medical record documents was 57.4% and 42.5% were incorrect. Readability review of ER assessment as much as 63.2%, assessment of Inpatient as much as 56.3%, CPPT as much as 60.9%, approval for action as much as 77%, reports of anesthesia as much as 68.9%. 3 forms of completeness review are complete, namely Education Assessment, rejection and education form (100%). Suggestions in this study are that review officers must be more assertive to remind every doctor or other medical personnel to pay attention to the accuracy of the restoration, the legibility of medical record files and the completeness of medical record documents. As well as regularly socializing the elements of the MIRM 13.4 assessment.